A study on the relationship between personality traits and innovative work behavior at Tabung Haji in Terengganu / Farah Waheeda Wahairi - Wahairi, Farah Waheeda (Faculty of Business Management, 2018)
This study was conducted at Tabung Haji Kerteh, Terengganu. The purpose of this study is to investigate the relationship between big five personality traits and innovative work behavior. The five personality traits are conscientiousness, agreeableness, neuroticism, openness to experience and extraversion. Method that had been used for this study was simple random sampling. The total population number of employees are 60 people, while the sample is 59 workers that working at Tabung Haji in Terengganu. Based on (Krecjie & Morgan, 1970), the sample size for 60 people are 52 people. To more detail about the finding of this study, please refer to next page. According to the result presented for this study, all the personality traits have their different effect towards employees within in the organization and each of these personality traits has some kind of relationship with innovative work behavior either positive or negative result. Based on the finding and discussion about this study, the result shown that the strongest relationship among the big five personality traits and innovative work behavior is Openness to experience with most of the employee in Tabung Haji possessed openness personality traits which are they are more likely to share their opinions and can accommodate with other people. For the weakest relationship among the big five personality traits and innovative work behavior are Conscientiousness. It can be described as the staffs in Tabung Haji are not prefer toward innovative work behavior.